Practitioner Profile: Roseann Adams - Roseann Adams (Journal of Financial Therapy, 2017)
Roseann Adams was born into a working-class Italian immigrant family in Chicago. Her father had been very poor as a child and delighted in the opportunities he found to earn money and provide for his family. Money was not a taboo topic in their household. From a young age she and her younger brothers were exposed to information about their family income, savings, spending, and debt. The children were often in on financial decision-making. It surprised Roseann when she learned that other kids she knew did not have similar information about their own family’s financial matters. She grew up with an appreciation for the value and power of money and remembers looking forward to the experience of earning her own income.